The secret blog of Raisin Rodriguez - Goldschmidt, Judy. (New York : Razorbill, 2005)
In a weblog she sends to her best friends back in Berkeley, seventh-grader Raisin Rodriguez chronicles her successes and her more frequent humiliating failures as she attempts to make friends at her new Philadelphia school.
Accelerated Reader AR
Keywords: Blogs -- Fiction; Interpersonal relations -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Humorous stories